Development of Electric Vehicle Charging Infrastructure in Indonesia to Achieve the Target of Nationally Determined Contribution by 2030 - Anshori, Muhamad Rizky; Boedoyo, M. Sidik; Saputro, Guntur Eko (Jurnal Ecoment Global, 2024)
Objective: This Study aims to identify the current condition of the electric vehicle charging infrastructure in Indonesia and make predictions to achieve the 2030 Nationally Determined Contribution (NDC) target. Design/Methods/Approach: The method used in this research is literature review, where the author conducts a study of literature in a number of journals and articles related to the research theme which is Development of Electric Vehicle Charging Infrastructure in Indonesia to Achieve the Target of Nationally Determined Contribution by 2030. There are several stages conducted in this research such as data collection, data analysis and drawing conclusions. These stages are carried out to determine the development of the existing conditions of Electric Vehicle Charging facilities in Indonesia to achieve the target of Nationally Determined Contribution by 2030. Findings: Considering the target number of electric vehicles in 2030, which is 600 thousand electric cars and 2.45 million electric two-wheelers, and the charging time or battery exchange time for electric vehicles, it is estimated that Indonesia needs to build 76,562.5 Public Electric Vehicle Charging Stations (PEVCS) for electric two-wheelers and 18,750 Public Electric Vehicle Charging Stations (PEVCS) for electric cars to support the 2030 National Determined Contribution target. As for the battery exchange system for electric two-wheelers, 17,014 Public Electric Vehicles Battery Exchange Stations (PEVBES) are needed to support the 2030 National Determined Contribution target. Originality/Value: This study builds upon previous research that discusses the condition of electric vehicle infrastructure in Indonesia, by adding predictions regarding the amount of infrastructure needed to meet the 2030 Nationally Determined Contribution (NDC) target. Practical/Policy implication: The research findings have significant implications for management and business practices, as well as policy aspects. In developing Public Electric Vehicle Charging Station facilities, there are many things that stakeholders need to consider, such as; Expanding the coverage of Public Electric Vehicle Battery Exchange Station facilities in rural areas, Establishing battery standards for Electric Vehicles to become a specific type of battery for Electric Vehicles that use a battery exchange system, Create battery exchange facilities for 4-wheeled vehicles.